Illum oportet crescere: o processo de recristianização no norte do Rio Grande do Sul (século XX) - Balzan, Jonas (2021)
This paper seeks to discuss the process of re-Christianization in the northern part of the state of Rio Grande do Sul during the 20th century. To this end, we go back to the 19th century to understand two concepts that we consider key to understanding the Roman Catholic Church (Roman Catholic Church), up until at least the Second Vatican Council (1962-1965). Starting from the concepts of Royal Patronage and Ultramontanism, we outline the historicity of the Roman Catholic Church, which after the Proclamation of the Republic (1889) developed new strategies, not only for its conservation, but also for its expansion. Among these strategies, we gave special emphasis to the creation of new dioceses, since it was through these that the plans to re-Christianize Brazilian society became effective. In the north of the State of Rio Grande do Sul, after a process that had already been taking shape, re-Christianization only became visible with the creation of the Diocese of Passo Fundo, in 1951, and gained strength with the actions of Dom João Cláudio Colling, its first bishop (1951-1981). Dom Cláudio, as he signed and became known, was the great articulator of the process of strengthening Roman Catholicism throughout its ecclesiastical jurisdiction. Being an excellent bishop strategist, he led the way in several areas, notably in the fields of health and education. In any case, since our main objective is the process itself, and not its articulator, we work essentially with his pastoral work and the emphasis of Restoring all in Christ. Dom Cláudio not only re-Christianized but also concerned himself with maintaining this reinvigorated Catholicism. To this end, he devised some tools that could help in the preservation of this system. Thus, based on the analysis of documents, especially the local-regional press, we will highlight Dom Colling's performance in the pastoral field, which aimed not only at consolidating the re-Christianization process, but also at preserving it in the northern region of Rio Grande do Sul.